A gamma type distribution involving a confluent hypergeometric function of the second kind - Fereira, Johan; Salinas, Susana (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In the present work a new gamma type distribution is obtained which involves a confluent hypergeometric function of the second kind. A generalized form of the incomplete gamma function and its complementary are introduced to obtain some statistical functions. The associated statistical functions with the probability density function are deduced such as the k-moment, expect value, risk function, half-life function and other special cases.